To solve the equation \( 25x^2 - 196 = 0 \) using the difference of squares pattern, we first recognize that this can be rewritten in the form \( a^2 - b^2 = 0 \).
Notice that:
\[ 25x^2 = (5x)^2 \quad \text{and} \quad 196 = 14^2 \]
So we can rewrite the equation as:
\[ (5x)^2 - 14^2 = 0 \]
This can be factored using the difference of squares formula:
\[ (a^2 - b^2) = (a - b)(a + b) \]
Thus, we have:
\[ (5x - 14)(5x + 14) = 0 \]
Setting each factor equal to zero gives us:
-
\( 5x - 14 = 0 \)
- Solving for \( x \) gives \( 5x = 14 \) or \( x = \frac{14}{5} \).
-
\( 5x + 14 = 0 \)
- Solving for \( x \) gives \( 5x = -14 \) or \( x = -\frac{14}{5} \).
Therefore, the solutions to the equation are:
\[ x = \frac{14}{5}, \quad x = -\frac{14}{5} \]
The correct answer is: C) \( x = -\frac{14}{5} \), \( x = \frac{14}{5} \).